Maxillofacial injuries due to motorcycle accidents from suburban Nigeria. Issue 1 (January 2023) - Adebayo, Ezekiel Taiwo; Fomete, Benjamin; Adelusi, Emmanuel Adetolu; Ahaji, Lilian Ejije; Nnawuhie, Ukachi Chiwendu
Abstract: Objectives: To assess causes, pattern and severity of maxillofacial injuries sustained during road traffic accidents including helmet use and riding status among motorcyclists for comparison to previous studies. Methods: A descriptive study was conducted between January 2020 and December 2021 at two suburban Nigerian treatment centres. Data was collected on demographics; helmet use, whether rider or pillion passenger; and cause of motorcycle accident. There was clinical examination and reviews of radiological investigations. Maxillofacial trauma was scored according to the FISS described by Bagheri et al. (2006) [12]. Results: The study had 55 participants (37 riders and 18 pillion passengers), aged 5–73years (mean 32.8years) with more males (89.1 %). One patient (1.8 %) reported helmet use. Bike-to-bike accidents were the most frequent (56.4 %). More soft tissue injuries were lacerations (32, 59.3 %) than abrasions (15, 27.8 %). There were 122 bone fracture, the fracture to patient ratio was 2.5:1. Mandibular (40.5 %), dentoalveolar (22.1 %) and maxillary fractures (13.9 %) were common. Most common sites of concomitant injuries was the lower limbs (50.0 %). Most had moderate/ severe FISS, mean 4.6 with significant association between FISS and gender (p = 0.024) and riding status (p = 0.013). Conclusion: Helmet use among the study population was very low and the maxillofacial fracture to patient ratio was relatively high compared to prior Nigerian studies. Males and riders sustained more of moderate/severe maxillofacial injuries. Public enlightenment and enforcement of road traffic laws among motorcyclists to reduce maxillofacial injuries in Nigeria are advocated.